The librarians. Season two [videorecording (DVD)] - Roskin, Mark; Rowe, Courtney (Director); Kane, Christian, 1974-; Booth, Lindy; Romijn, Rebecca, 1972- (Sony Pictures Home Entertainment, 2016)
A team of librarians working for an ancient organization hidden under the Metropolitan Public Library recover artifacts and fight against supernatural threats as they investigate various mysteries.